The Properties of Brown Marine Algae Sargassum turbinarioides and Sargassum ilicifolium Collected From Yogyakarta, Indonesia - Artemisia, Rahma; Nugroho, Akhmad Kharis; Setyowati, Erna Prawita; Martien, Ronny (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Brown marine algae are the prominent source of marine natural products that have bioactive metabolites. Sargassum turbinarioides and Sargassum ilicifolium were dominated in Indonesia as brown marine algae that well known as a source of fucoidan. The samples were collected from Gunungkidul, Yogyakarta, Indonesia. In this study, we investigated and identified the yield of aqueous crude and purified extracts using different extraction temperatures (60°C, 70°C, 80°C, 90 °C). The highest yield of S. turbinarioides crude extract (7.36%) was obtained at temperatures 90 and 80 °C while the highest yield of S. ilicifolium was 3.49 % at 80 °C. The presence of sulfate polysaccharide in Sargassum turbinarioides is 3,78 % and Sargassum ilicifolium is 2,93 %. Each of the extract was screened using phytochemical detection, Thin Layer Chromatography (TLC) and Fourier transform infrared spectroscopy (FT-IR) analysis. The phytochemical detection indicated that Sargassum ilicifolium has bioactive metabolites such as carbohydrates, proteins and amino acids, terpenoid, phenolic compounds, and flavonoids. The FTIR spectrum of the S. turbinarioides and Sargassum ilicifolium extract refer to the presence of ester sulfate groups through showing peaks at 1300 to 1200 cm-1 and 980 to 950 cm-1. The result indicated that Sargassum turbinarioides and Sargassum ilicifolium contain of sulfate polysaccharide were prospect a biological activities to use for the development of marine nutraceutical drugs especially as antioxidant.